M. A. Fedorova, M. W. Tofique, A. Löf, C. Millward, Z. Günther. Testing and calculation of impact fatigue strength of Flap-X and SS 716 flapper valve steel grades / trans from Engl. M. A. Fedorova - M. A. Fedorova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
During the operation of reciprocating compressors, the flapper valve opens and closes under fluid pressure and flow. As it closes, it strikes against the valve seat, generating stresses and noise. This cycle of loading produces bending and impact fatigue stresses in the reed. This load pattern is repeated billions of times during the service life of a compressor and it defines the service life and reliability. The goal of this study was to calculate the impact fatigue strength of the Flap-X and the SS 716 grades and, to provide the compressor manufacturers with the information they can use to specify a steel grade to be used in their compressors, for reliable service. Impact fatigue tests were conducted on a custom-built impact fatigue test rig that used air pulses to produce movement of the reed valves manufactured by a major European compressor manufacturer Nidec Global appliance GmbH, at a frequency of 315 Hz and pulse width of 2,2 milliseconds. The testing was conducted according to the staircase test method detailed in the International Standard SS-ISO 12107:2012. The impact fatigue strength of the Flap-X and SS 716 steel valves was calculated in terms of the impact velocity according to the modified staircase test method in the standard. The test results and their statistical analysis showed that the impact fatigue strength of the Flap-X grade was higher compared to the SS 716 grade. The calculation and testing of the impact fatigue strength of the flapper valve steel grades could help the compressor designers to select the optimum material for their compressor designs, to provide reliable service. The higher impact fatigue strength of the Flap-X grade, lower failure rate and longer impact fatigue life will allow the compressor manufacturers to design thinner valves, as Flap-X can sustain higher impact fatigue stresses reliably for longer time and, at the same time help reduce noise, as thinner valves produce less noise for a given pressure and frequency.